Odpowiedź :
Odpowiedź:
B
Szczegółowe wyjaśnienie:
Należy usuwać niewymierność "na raty".
[tex]\frac{1}{\sqrt3+\sqrt2+1}*\frac{\sqrt3+\sqrt2-1}{\sqrt3+\sqrt2-1}=\frac{\sqrt3+\sqrt2-1}{(\sqrt3+\sqrt2)^2-1}=\frac{\sqrt3+\sqrt2-1}{3+2\sqrt6+2-1}=\frac{\sqrt3+\sqrt2-1}{2\sqrt6+4}*\frac{2\sqrt6-4}{2\sqrt6-4}=\\=\frac{2\sqrt{18}-4\sqrt3+2\sqrt{12}-4\sqrt2-2\sqrt6+4}{24-16}=\frac{6\sqrt2-4\sqrt3+4\sqrt3-4\sqrt2-2\sqrt6+4}{24-16}=\frac{2\sqrt2-2\sqrt6+4}{8}=\\=\frac{2+\sqrt2-\sqrt6}{4}[/tex]
Szczegółowe wyjaśnienie:
Starałam się jak najbardziej rozpisywać :)